2012
DOI: 10.1242/jcs.086421
|View full text |Cite
|
Sign up to set email alerts
|

miR-132 regulates the differentiation of dopamine neurons by directly targeting Nurr1 expression

Abstract: SummaryAlthough it is well established that embryonic stem (ES) cells have the potential to differentiate into dopamine neurons, the molecular basis of this process, particularly the role of microRNAs (miRNAs), remains largely unknown. Here we report that miR-132 plays a key role in the differentiation of dopamine neurons by directly regulating the expression of Nurr1 (also known as nuclear receptor subfamily 4 group A member 2; Nr4a2). We constructed a mouse ES cell line CGR8, which stably expresses GFP under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 49 publications
(66 reference statements)
7
114
0
Order By: Relevance
“…Salta E et al have noticed that miR-132 dampens radial glial (embryonic neural stem cells) proliferation but promotes oligodendrocyte differentiation by fine tuning Notch signaling [31]. Decreased expression of miR-132 promotes neuronal differentiation of embryonic stem cells (ESC) [32], that was in line with the result we obtained in NSCs. Overexpression of miR-132 showed impaired neuronal differentiation and enhanced glial differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…Salta E et al have noticed that miR-132 dampens radial glial (embryonic neural stem cells) proliferation but promotes oligodendrocyte differentiation by fine tuning Notch signaling [31]. Decreased expression of miR-132 promotes neuronal differentiation of embryonic stem cells (ESC) [32], that was in line with the result we obtained in NSCs. Overexpression of miR-132 showed impaired neuronal differentiation and enhanced glial differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…Both of these examples suggest that miRNA/transcription factor loops could be a common theme in dopaminergic neuron differentiation. This hypothesis is further supported by the discovery of a functional interaction between miR-132 and yet another transcription factor important for differentiation of dopaminergic neurons, Nurr1 (Nr4a2) (Yang et al, 2012). …”
Section: Box 1 Insights From Dicer Conditional Knockoutsmentioning
confidence: 86%
“…MAP2: 5´-CCAATGGATTCCCATACAGG-3´; 5´-CTGC-TACAGCCTCAGCAGTG-3´. The real-time PCR GO promotes the differentiation of mouse ESCs to dopamine neurons Preliminary Communication was performed according to our previous report [26]. All reactions were repeated three times.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…Given the existing evidence of nanomaterials on stem cell proliferation and differentiation, we tested the potential induction effect of CNTs, GO and GR on the differentiation of dopamine neurons in this study. Using the previously established tyrosine hydroxylase (TH)-GFP reporter ESCs [26], we found that only GO significantly promotes dopamine neuron differentiation. Furthermore, we documented that the effect of GO on the dopamine neuron differentiation process is dose dependent and it has a profound impact on dopamine-related gene expression.…”
mentioning
confidence: 99%